Late‐life reproduction in an insect: Terminal investment, reproductive restraint or senescence. Issue 1 (28th October 2020) - Jehan, Charly; Sabarly, Camille; Rigaud, Thierry; Moret, Yannick
Abstract: The terminal investment, reproductive restraint or senescence theories may explain individual late‐life patterns of reproduction. The terminal investment hypothesis predicts that individuals increase reproductive allocation late in life as prospects for future survival decrease. The other two hypotheses predict reduced reproduction late in life, but for different reasons. Under the Reproductive Restraint hypothesis, individuals restrain their reproductive effort to sustain future survival and gain more time for reproducing, whereas under the Senescence process, reproduction is constrained because of somatic deterioration. While these hypotheses imply that reproduction is costly, they should have contrasted implications in terms of survival after late reproduction and somatic maintenance. Testing these hypotheses requires proper consideration of the effects of age‐dependent reproductive effort on post‐reproduction survival and age‐related somatic functions. We experimentally tested these three hypotheses in females of the mealworm beetle, Tenebrio molitor, an iteroparous and income breeder insect. We manipulated their age‐specific allocation into reproduction and observed the effects of this manipulation on their late‐life fecundity, post‐reproduction survival and immunocompetence as a measurement of somatic protection. We found that females exhibit age‐related decline in fecundity and that this reproductive senescence is accelerated by a cost of early reproduction. The cost of reproduction had no significant effect on female longevity and their ability to survive a bacterial infection, despite that some immune cells were depleted by reproduction. We found that female post‐infection survival deteriorated with age, which could be partly explained by a decline in some immune parameters. Importantly, females did not increase their reproductive effort late in life at the expense of their late‐life post‐reproduction survival. Late‐life reproduction in T. molitor females is senescing and not consistent with a terminal investment strategy. Rather, our results suggest that females allocate resources according to a priority scheme favouring longevity at the expense of reproduction, which is in line with the reproductive restraint hypothesis. Such a priority scheme also shows that a relatively short‐lived insect can evolve life‐history strategies hitherto known only in long‐lived animals. This puts in perspective the role of longevity in the evolution of life‐history strategies. Abstract : The existence of a priority scheme favouring longevity at the expense of reproduction shows that a relatively short‐lived insect like Tenebrio molitor can evolve life history strategies hitherto known from long‐lived animals only, putting in perspective the role of longevity in the evolution of life history strategies.